A double‐hit High‐grade B‐cell lymphoma with three‐way translocation t(3;8;14)(q27;q24;q32) involving BCL6, MYC, and IGH. Issue 12 (26th October 2018) - De Paoli, Elena; Bandiera, Laura; Ravano, Emanuele; Cesana, Clara; Grillo, Giovanni; Mancini, Valentina; De Canal, Gabriella; Bonoldi, Emanuela; Soriani, Silvia
Key Clinical Message: We describe an High‐grade B‐cell lymphoma case, in which a complex translocation t(3;8;14) with effects on the genes BCL6, MYC, and IGH, was detected. This case could be the first double‐hit lymphoma with a single chromosome rearrangement causing the double effect with three genes involved. Abstract : We describe an High‐grade B‐cell lymphoma case, in which a complex translocation t(3;8;14) with effects on the genes BCL6, MYC, and IGH, was detected. This case could be the first double‐hit lymphoma with a single chromosome rearrangement causing the double effect with three genes involved.